Penerapan Metode Discovery Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa - Eka Rosdianwinata (Universitas Mathla'ul Anwar Banten, 2015)
This study aims to examine whether there is relationship between the ability of mathematical problem solving with emotional intelligence at students of Junior High School.The hypothesis of the study is that the students’ ability of mathematical problem solving which using discovery strategy in learning is better than students’ ability which using conventional learning strategy. The sample obtaining of the study is conducted by purposive sampling at the second year students of one of SMP in Purwakarta regency in academic years 2013/2014. The method used in this study is a qualitative study that quantified where quantitative method it self is used top rove the hypothesis by comparing the two classes with different treatments by using quasi experiment research design. The results hows that the mathematical problem solving ability of students who learning using the discovery method is the same as the conventional learning students.The results obtained from the mathematical problem solving ability of students who have completed the learning with discovery method, those quality does not in crease well. Although the obtained scores a chieved by students at the beginning of learning until the end of the lesson for the better.